THE IMPORTANCE OF DIGITALIZATION IN THE MILITARY FIELD - Azimov J.T. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article presents the essence and advantages of digitalization in the military sphere. Nowadays, digital technologies have rapidly entered all spheres of our lives. In his address to the Oliy Majlis on January 25, 2020, President Shavkat Mirziyoyev spoke about the important priorities of developing digital technologies in our country: “In order to accelerate the further development of science in our country, to educate our youth in deep knowledge, high spirituality and culture, and to form a competitive economy, in 2020 we will continue to increase the level of science, education, and the digital economy.” [1]. New digital technologies are considered the basis of an information society.